2018
DOI: 10.1080/15226514.2017.1365349
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity of tin mine waste and accumulation of involved heavy metals in common buckwheat (Fagopyrum esculentum Moench)

Abstract: Extraction and processing of cassiterite (SnO) left large tailings with high concentrations of tin, tungsten, molybdenum and lithium. Information on the phytotoxicity of mine waste is important with regard to ecological hazards. Exposure studies help to identify plants useful for the stabilization of waste tips and the phytomining of metals. A greenhouse study was performed using a dilution series of mine waste and four crops, a halophytic and a metallophytic species to derive dose response curves. Based on ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…There are many regions in Europe with large deposits of mine wastes, and many unmanaged sites contaminated with metals. Scientists have suggested that wastelands could be prepared for regular biomass production using metal tolerant vegetation or bioenergy crops (e.g., oilseed rape, buckwheat, willow) [28]. Soils that are polluted by metals and require remediation often surround historical industrial and mining plants.…”
Section: Discussionmentioning
confidence: 99%
“…There are many regions in Europe with large deposits of mine wastes, and many unmanaged sites contaminated with metals. Scientists have suggested that wastelands could be prepared for regular biomass production using metal tolerant vegetation or bioenergy crops (e.g., oilseed rape, buckwheat, willow) [28]. Soils that are polluted by metals and require remediation often surround historical industrial and mining plants.…”
Section: Discussionmentioning
confidence: 99%
“…Pb'den en az etkilenen bitki türünün güve otu, ayçiçeği ve hint fasulyesinin orta derece toleranslı, karabuğdayın ise en hassas tür olduğu belirlenmiştir (Alves vd., 2016). Kalay madeni atıklarının fitotoksik etkisinin araştırıldığı bir çalışmada ise Cd ve Cu uygulanan karabuğday bitkisinin Cd'den daha fazla etkilendiği ve yüksek miktarda Cd'nin kök ve sürgün taze-kuru ağırlığında azalmaya neden olduğu belirtilmiştir (Franzaring, 2018). Ayrıca Liu vd.…”
Section: Kök Ve Gövde Uzunluklarıunclassified